Estado del arte en la aplicación del e-business como modelo de gestión, para la mejora del servicio al cliente en el negocio de traslado de mercancía por vía terrestre - González Vásquez, Luis Alfredo (2015)
The present investigation work has been elaborated with the purpose of applying the electronic tools that will allow us in the immediate future to reduce costs, time, space and that these applications helped us to consolidate like a company that takes the vanguard in our business item. Transport Line, it is not unaware to this technological advance and knowing that applying this tool in their operations, he/she will help us to lead the market in the transfer of goods. In this work we seek to show the big competitive and comparative ventajes in their integral application in all their context from the strategic and operational point of view, creating an organization guided to the I redraw of processes, redraws of flows of value, I redraw corporate and a strategic Visionamiento with the collaboration of the human capital and the technology application will be able to reach a modern and functional company, offering correct, opportune and reliable information about the requirements and necessities that our clients request.